RESISTENSI PENDUDUK PERDESAAN DALAM CERITA KESEHARIAN DI KALI LORO - Gutomo Bayu Aji (Populasi, 2000)
This analysis is revision of fieldwork journals during the exploration stages at Kali Loro collected in 1999. Data have been acquired through friendly approach, direct observation, and unstructured personal interview. Data analysis was carried out by applying the resistence concept which is defined by James C. Scott of daily narrations in Kali Loro. From the three presented narrations, they show that the kind of resistence contended by Kali Loro inhabitants is in concord with the nature of resistence proposed by Scott. While the first and the second narrations are in accordance with the hidden transcript category, the third one conforms with public transcript category. The resistence takes place in the forms of superior and subordinate structures in a meeting point process of the conflict of interest between class identity and class awareness.